An African Exploration of the East Asian Education Experience - Fredriksen, Birger; Tan, Jee Peng (Washington, DC : World Bank, 2012)
Contents of the report are as follows: East Asia education study tour: an overview of key insights by Birger Fredriksen, and Tan Jee Peng. Education in Africa: knowledge makes the difference by Mamadou Ndoye. Education in Singapore: developments since 1965 by Goh Chor Boon, and S. Gopinathan. Education in Vietnam: development history, challenges, and solutions by Nguyen Quang Kinh, and Nguyen Quoc Chi. Education in the Republic of Korea: approaches, achievements, and current challenges by Chong Jae Lee. Education in Thailand: improving secondary education by Luis Benveniste. Education in Ireland: evolution of economic and education policies since the early 1990s by Daniel O' Hare.